Research and Application of Airlift Pump to Operate Aquaponics - Trinh, Van Dung; Vo, Thi My Lan; Nguyen, Sy Xuan An; Pham, Van Hung (Journal of Technical Education Science, 2023)
This paper presents the results of a study on the use of an airlift pump in aquaponics, a model that has been applied and developed for organic food production. Airlift pumps, which are commonly used in the mining industry for pumping liquids such as water and oil, have recently been adopted for use in aquaponics systems. Airlifts offer several advantages over other types of pumps, including a simple and compact design with no moving parts, making them suitable for hanging systems in shallow water. Airlifts also play a dual role in transporting liquids and saturating dissolved oxygen content in water, which is essential for the organisms in the aquaponics system to thrive. To promote these benefits, it is crucial to choose the correct mode of operation for the aeration pump; otherwise, it may decrease efficiency and increase operating costs. In this study, an airlift pump, which combines an aquaponic pump, aerator, and duct system into one compact unit, was used. The experiment was conducted using a riser pipe of different diameters (D = 24, 30, 36, 48 mm), a height (h + H) of 2000 mm, an air pipe with a diameter of 15 mm, compressed air pressure ranging from 0.5 to 4.0 kg/cm2, gas consumption (V) between 0.1 to 1.0 m3/h, and a pump capacity (Q) of 5-39 L/min. The results show that the greatest lifting height can be achieved with a riser pipe diameter of 30-36 mm. At an airflow rate of 0.8-0.9 m3/h and various compression pressures, the dip coefficient of 0.285 produces a maximum pumping capacity of 25-30 L/min.